Tutoria para alunos com baixo aproveitamento acadêmico e o desenvolvimento de cognições e estratégias de leitura e escrita - Buzetti, Miryan Cristina (2010)
Studies have identified a set of teaching conditions associated with tutoring effectiveness focused in book reading for preventing the writing and reading failuse as a form of supporting teaching to regular education. In this study was sought to 1) to verify the connection between the education condition offered in a tutoring focused in the book reading and education conditions associated to reading skills and writing improvements; 2)evaluate the tutoring effects on reading and writing skills on students whit low achievement in early literacy from data on performance throughout the tutoring sessions and the performance presented on evaluated tasks by specific assessment tools applied at the beginning, intermediate and final stage of the intervention; 3) describing the progress of reading strategies used by students. The participants were four students in the same second grade class of public elementary school, they were selected due to the low reading and writing achievements. During 17 weeks in a semester, the students attended 3 tutoring weekly sessions around 30 minutes each. In each session the interaction between the tutor and the student was directed in order to make possible for the students to have the commitment in a book presentation which isn´t still familiar made by the tutor, independent reading made by the student of a familiar book and a non familiar one, the involvement in activities for the recognition of letters, syllables and words, speaking and writing sentences and stories, decomposition and recomposition of sentences and stories. The results allow us to conclude the teaching conditions offered responded satisfactorily to the guidelines predict by the experts and professionals who work with tutoring focused in reading. Is was verified the tutor had a previous training to conduct the reading and writing activities in the tutoring sessions. Performing as a supporter in a students learning, encourage the student´s strengths in terms of reading and writing for each student, and systematically made adjustments that me the specific difficulties of each student, helped the students to read accurately through the use of suitable books to the level of difficulty of each student. Regarding to the effects on the students, the results indicate a substantial increase in the percentage correct reading of words and texts, writing dictated words and in the use of appropriate reading strategies such as self-correction and search for meaning. The teacher´s report about the students achievement in the classroom indicate a recognition of the reading an writing students improvement due to the support provide by tutoring.